Criminal Law: a critical approach - Capers, Bennett (Eagan: Foundation Press, West Academic, 2023)
Increasingly, students and faculty are demanding more critique when it comes to the study of criminal law, especially with respect to issues of race, gender, disability, sexuality, and class. This challenging, yet student-friendly, casebook--the first authored solely by Black men--answers this demand. Criminal Law: A Critical Approach provides clear articulations of core criminal law doctrines and concepts, while at the same time encouraging students to think critically about a host of issues tied to the world in which we live. Against the backdrop of mass incarceration, over-criminalization, and disparities along lines of race, gender, class, sexuality, and disability, this casebook: encourages students to see the criminal law as a system; uses the criminal system pyramid to introduce students to the range of social controls inherent in the criminal system; addresses sources and topics of criminalization that are often overlooked by more traditional casebooks, including non-violent and victimless crimes that constitute the bulk of real-world criminal prosecutions; provides students with the tools to critically engage arguments for and against prison abolition, defunding the police, and alternatives to incarceration; and encourages students to think comparatively through discussion of how legal systems have addressed crime at other times and in other countries. With its mixture of doctrine, theory, and policy, this is a textbook designed to provide a diverse range of resources to help professors challenge the students of today and prepare the lawyer-leaders of tomorrow.
Keywords: Criminal law - United States; Criminal law -- United States -- Interpretation and construction; Sociological jurisprudence -- United States